Application Of The Moral Reasoning Model To Increasing The Courage Of Expressing Opinions On Content PPKn Students Of Class V SDN 047 Inpres Baurung Polewali Mandar District - Nurfaizah Nurfaizah; Syamsuryani Eka Putri Atjo; Musdalifah Musdalifah (International Journal of Elementary School Teacher, 2023)
The problem in this research is the low success in expressing income experienced by students in the learning process. From these problems, there is a goal to be achieved in the research, namely the application of a moral reasoning model to increase the courage to express opinions in class V at SDN 047 Inpres Baurung, Polewali Mandar Regency. The approach used is a qualitative approach and this type of research is Classroom Action Research (CAR) which is carried out in two cycles and each cycle is carried out in two meetings. The stages of activities carried out include the planning stage, the implementation stage, the observation stage, and the reflection stage. Data collection techniques and procedures used are observation and documentation. The subjects of this study were class V teachers and 22 students consisting of 10 boys and 12 girls. The data analysis used is quantitative and descriptive qualitative. The results showed that there was an increase in teacher activity The first cycle of the first meeting was in the adequate category and the second meeting was in the sufficient category while in the second cycle the first meeting was in the good categoryand the second meeting was in the good category and in the first cycle of student learning activities the first meeting was in the less category and the second meeting was in the sufficient category while in the second cycle the first meeting was in the good category and the second meeting was in the good category. From the results of this study, it can be concluded that the application of the moral reasoning model can increase the courage to express students' opinions.